2012
DOI: 10.1177/0017896912450249
|View full text |Cite
|
Sign up to set email alerts
|

Impact of norm perceptions and guilt on audience response to anti-smoking norm PSAs: The case of Korean male smokers

Abstract: Objective: To examine how norm appeals and guilt influence smokers’ behavioural intention. Design: Quasi-experimental design. Setting: South Korea. Method: Two hundred and fifty-five male smokers were randomly assigned to descriptive, injunctive, or subjective anti-smoking norm messages. After they viewed the norm messages, their norm perceptions, guilt and behavioural intention were measured. Results: The study revealed several findings: (1) injunctive norm perceptions significantly affected behavioural inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 25 publications
(28 reference statements)
1
15
0
Order By: Relevance
“…We used six items to measure perceived descriptive norms [ 30 ], which were defined as the perception of smoking prevalence/indoor smoking prevalence of other people (including close social networks and the general public). We asked participants three items about smoking: ‘How many of your friends (or, ‘typical Japanese individuals of the same sex’, or ‘typical Japanese individuals of the same sex and from your generation’) do you think would smoke?’ We asked another three items about indoor smoking: ‘How many of your friends (or, ‘typical Japanese individual of the same sex’, or ‘typical Japanese individual of the same sex and from your generation’) do you think would smoke indoors?’ Responses were provided using a 7-point Likert scale ranging from 0% to 100% in 20-point increments (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used six items to measure perceived descriptive norms [ 30 ], which were defined as the perception of smoking prevalence/indoor smoking prevalence of other people (including close social networks and the general public). We asked participants three items about smoking: ‘How many of your friends (or, ‘typical Japanese individuals of the same sex’, or ‘typical Japanese individuals of the same sex and from your generation’) do you think would smoke?’ We asked another three items about indoor smoking: ‘How many of your friends (or, ‘typical Japanese individual of the same sex’, or ‘typical Japanese individual of the same sex and from your generation’) do you think would smoke indoors?’ Responses were provided using a 7-point Likert scale ranging from 0% to 100% in 20-point increments (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…We used 12 items to measure perceived subjective norms [ 30 ], which were defined as the perception of whether family and friends approve of one’s own smoking behaviour. The questions were: ‘To what extent do/does your (friends/family/colleagues) approve of the following behaviours you engage in: (1) smoking, (2) smoking in your house, (3) smoking in front of others (or public places), and (4) smoking in your workplace?’ Responses were provided using a 5-point Likert scale ranging from ‘1 = strongly disapprove ’ to ‘5 = strongly approve ’.…”
Section: Methodsmentioning
confidence: 99%
“…Within this framework, scholars have sought to identify what influences pro-environmental behaviors in hospitality and tourism contexts. Researchers who have modeled associations among cognitive triggers [36,39,40], affective triggers [41,42], personal norms [2,43], and normative triggers [44][45][46] in the formation of visitor intentions to behave in pro-environmental ways have suggested that cognitive, affective, and normative triggers are critical in activating norms. In particular, affective triggers and personal norms included mediating impacts, and anticipated feelings and moral obligations were particularly important in determining intentions.…”
Section: Sustainability In the Festival Settingmentioning
confidence: 99%
“…However, in the case of nicotine dependence, such self‐stigma may spur some individuals to attempt to quit. Data from smokers in Korea show that guilty feelings were positively and directly related to behavioral intention . The more the participants felt guilty after seeing each announcement, the more likely they were to search for an anti‐smoking public service to help them quit, and the higher their intention to quit smoking .…”
Section: Anti‐smoking Pressure and Stigma Attached To Smokingmentioning
confidence: 99%
“…There is also a further issue that deserves further exploration, which is how people see their own identity as smokers in other settings. 56 In summary, there is evidence from qualitative studies 45,56 showing that, despite the undeniable positive effects of current antismoking legislation and related peer pressure within several countries, 46,55 smokers may experience great difficulty in dealing with their failure to quit smoking, and this should also be a public health concern. These variations, both at individual and cultural levels, influence the search for receiving and understanding guidance regarding smoking in health-care environments.…”
Section: Anti-smoking Pressure and Stigma Attached To Smokingmentioning
confidence: 99%